Multiwavelength observations of the extraordinary accretion event AT2021lwx - Wiseman P; Wang Y; Honig S; Castro-Segura N; Clark P; Frohmaier C; Fulton MD; Leloudas G; Middleton M; Muller-Bravo TE; Mummery A; Pursiainen M; et al. (OXFORD UNIV PRESS, 2025)
We present observations from X-ray to mid-infrared wavelengths of the most energetic non-quasar transient ever observed, AT2021lwx. Our data show a single optical brightening by a factor >100 to a luminosity of 7 x 10(45) erg s(-1) and a total radiated energy of 1.5 x 10(53) erg, both greater than any known optical transient. The decline is smooth and exponential and the ultraviolet-optical spectral energy distribution resembles a blackbody with a temperature of 1.2 x 10(4) K. Tentative X-ray detections indicate a secondary mode of emission, while a delayed mid-infrared flare points to the presence of dust surrounding the transient. The spectra are similar to recently discovered optical flares in known active galactic nuclei but lack some characteristic features. The lack of emission for the previous 7 yr is inconsistent with the short-term, stochastic variability observed in quasars, while the extreme luminosity and long time-scale of the transient disfavour the disruption of a single solar-mass star. The luminosity could be generated by the disruption of a much more massive star, but the likelihood of such an event occurring is small. A plausible scenario is the accretion of a giant molecular cloud by a dormant black hole of 10(8)-10(9) solar masses. AT2021lwx thus represents an extreme extension of the known scenarios of black hole accretion.